Biochemical markers may identify preterm infants with a patent ductus arteriosus at high risk of death or severe intraventricular haemorrhage. Issue 6 (19th February 2008) - El-Khuffash, A; Barry, D; Walsh, K; Davis, P G; Molloy, E J
Abstract : Background: A patent ductus arteriosus (PDA) in preterm infants is associated with increased risk of intraventricular haemorrhage (IVH) and death. Cardiac troponin T (cTnT) and N-terminal-pro-B type natriuretic peptide (NTpBNP) are markers of cardiac function and can predict poor outcome in adults. Aims: To determine whether echocardiography and cTnT/NTpBNP levels at 48 h predict death before discharge or severe IVH in preterm infants with a PDA. Methods: Infants born <32 weeks' gestation or <1500 g underwent echocardiographic and cTnT/NTpBNP measurements at 12 and 48 h of life. Infants were divided according to their status at discharge: a closed PDA at 48 h, infants with a PDA at 48 h and IVH III/IV and/or death, and infants with a PDA at 48 h without IVH III/IV or death. Results: Eighty infants with a median gestation of 28 weeks (IQR 26.1–29.5) and birth weight 1.06 kg (0.8–1.21) were included. At 48 h, infants with a PDA and IVH III/IV and/or death had significantly higher median cTnT/NTpBNP levels compared to infants with a PDA without IVH III/IV and/or death and those with spontaneous PDA closure (NTpBNP 9282, 5121 and 740 pmol/l, respectively, p = 0.008, and cTnT 0.66, 0.25 and 0.13 µg/l, respectively, p = 0.027). There were no differences in echocardiographic parameters of PDA size, left atrial to aortic ratio (LA:Ao), left and right ventricular outputs between the PDA groups. Conclusions: NTpBNP and cTnT in conjunction with echocardiography may provide a basis for trials of targeted medical treatment in infants with a PDA.